Theo's Ambitions in The Case of Gabriel’s Murder in Alex Michaelides’ The Silent Patient - Daniel Gracia Maliangkay; Anik Cahyaning Rahayu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study discusses Theo Faber's ambitions in the Gabriel’s murder case in Alex Michaelides' The Silent Patient. This study aims to describe Theo's ambitions and the triggers of Theo's ambitions. This study uses the novel, The Silent Patient as the source of data. In answering the problems raised in this study, the writer uses a psychological approach and Ludwig Klages' psychological theory of personality. The approach and theory serve as a guide to analyze the data and reveal the phenomenons of ambitions in the novel. The extrinsic approach used is psychological approach, because the research discusses the psychological side of the characters. This study uses a qualitative descriptive method. The results of this study show that there are two ambitions that arise in Theo's character, to know Alicia's personality and to help Alicia deal with her case. Theo is very interested in Alicia's personality and he pays attention and finds out how Alicia's personality is. Theo, who is responsible for Alicia, wants to help Alicia, so she can talk and solve her case. There are two triggers for Theo's ambitions, feeling guilty and being a psychotherapist. Theo's feelings of guilt towards Alicia appears because of his actions in the past triggers his ambitions to take care of Alicia. Because Theo is a psychotherapist, he is very self-confident, and his work triggers his ambitions for Alicia. Even though many things have happened to Theo's ambitions, Theo still struggles to achieve his ambitions. Theo proves that he has a high desire and motivation to achieve his goal of ambitions. Theo is finally able to achieve his ambitions, which is to help Alicia to want to be willing to speak up.